Integrating Brand Gestalt and Customer Loyalty in Telecommunication Sector: The Mediating Role of Customer Satisfaction - Walean, Ronny H.; Pongoh, Helena; Mandagi, Deske (International Review of Management and Marketing, 2024)
This study examines how the four dimensions of brand gestalt—story, sensescape, servicescape, and stakeholders—influence customer satisfaction and loyalty within a telecommunication company context. The research employed a descriptive quantitative design, collecting primary data through a survey of 232 respondents who use Telkomsel Indonesia’s products and services. Data analysis was performed using Structural Equation Modeling (SEM) with the support of the SmartPLS statistical application. The findings reveal that the sensescape, servicescape, and stakeholder dimensions are crucial in determining customer satisfaction. Notably, only the sensescape dimension has a significant and positive impact on customer loyalty. These results suggest that Telkomsel should prioritize enhancing the sensescape, servicescape, and stakeholder components to improve customer satisfaction, with particular focus on sensescape to effectively boost customer loyalty.